Reaktualisasi Hukum Islam di Indonesia - Teguh Prawiro (STIT Muslim Asia Afrika, 2021)
It is a fact that the Muslims are the majority of Indonesia's population. Uniquely, the desire to apply Islamic law as a legal system for them only emerged from the minority group of this majority. There are several factors that can be assumed and identified to be the cause of this phenomenon. Among these factors, it seems that the most dominant is the internal condition of Islamic law itself which is felt to be unable to touch the values of justice for its people. Therefore, it must be realized the significance of reform or renewal of Islamic law in Indonesia towards a legal system that is more sensitive to the needs of Indonesian Muslims. One of them is by always paying attention to Indonesian values as a consideration for carrying out reforms. So that Indonesian Muslims can feel the justice and benefits that are born from its implementation. However, not all elements of Islamic law can be flexibly compromised with customary law systems. The elements referred to here are those included of constant teachings in Islamic law. Therefore, when local needs are confronted with the constant teachings in Islamic law, at least it will give two alternative forms of compromise with each other being in opposite poles. On the one hand, in order to fulfill their local (customary) needs, some Muslims beat Sharia with Sharia engineering. While at the other side, some Muslims still maintain the existence of constant teachings in Islamic law above their local needs with social engineering.